Analisis Implementasi Balanced Scorecard ( Perspektif Keuangan ) Pada PT. Bank Riau Kepri,Tbk Periode Tahun 2009 – 2012 - Hidayat Ricki; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The research was conducted on PT. Bank Riau Kepri,Tbk, Pekanbaru city. The purpose of this study is to analysis the implementation of the financial perspective of the balanced scorecard in PT. Bank Riau Kepri,Tbk period 2009-2012 because the balanced scorecard is a strategic management framework which is derived from the vision, mission, and strategy into four perspectives: financial, customer, internal business processes, and learning and growth which will result in long-term benefits for the company.This research is a descriptive study with a qualitative approach. Where no population and sample. This study using key informan to obtain the information needed. The data used are primary data and secondary data. The primary data obtained from interview with the Human Capital Division of PT. Riau Kepri,Tbk about the implementation of the balanced scorecard. Secondary data obtained from financial reports and then analyzed using financial ratios.From the analysis conducted known that the implementation of the balanced scorecard due of traditional management systems can no longer to used in dynamic environment. And from the analysis of financial ratios conducted also known that the financial condition of PT. Bank Riau Kepri,Tbk is unstable but very good overall. The biggest problem is the increasing non-performing loans at PT. Bank Riau Kepri, TbkKeywords: Implementation, Balanced Scorecard, Financial Perspective, Financial Ratios